Goodbye days [book club bag] : a novel - Zentner, Jeff (Crown Books for Young Readers, 2017)
Carver Briggs never thought a simple text would cause a fatal crash, killing his three best friends, Mars, Eli, and Blake. Carver can't stop blaming himself for the accident, and a judge is pressuring the district attorney to open up a criminal investigation. Eli's girlfriend, Carver's therapist, and Blake's grandmother ask Carver to spend a "goodbye day" with them to share their memories and say a proper farewell. As other families ask for their own goodbye day with Carver, will it mean making peace with their losses, or bring Carver one step closer to a complete breakdown-- and possibly prison?